Cortical thickness in obsessive–compulsive disorder: Multisite mega-analysis of 780 brain scans from six centres. (January 2017) - Fouche, Jean-Paul; du Plessis, Stefan; Hattingh, Coenie; Roos, Annerine; Lochner, Christine; Soriano-Mas, Carles; Sato, Joao R.; Nakamae, Takashi; Nishida, Seiji; Kwon, Jun Soo; Jung, Wi Hoon; Mataix-Cols, David; et al.
Abstract : Background: There is accumulating evidence for the role of fronto-striatal and associated circuits in obsessive–compulsive disorder (OCD) but limited and conflicting data on alterations in cortical thickness. Aims: To investigate alterations in cortical thickness and subcortical volume in OCD. Method: In total, 412 patients with OCD and 368 healthy adults underwent magnetic resonance imaging scans. Between-group analysis of covariance of cortical thickness and subcortical volumes was performed and regression analyses undertaken. Results: Significantly decreased cortical thickness was found in the OCD group compared with controls in the superior and inferior frontal, precentral, posterior cingulate, middle temporal, inferior parietal and precuneus gyri. There was also a group x age interaction in the parietal cortex, with increased thinning with age in the OCD group relative to controls. Conclusions: Our findings are partially consistent with earlier work, suggesting that group differences in grey matter volume and cortical thickness could relate to the same underlying pathology of OCD. They partially support a frontostriatal model of OCD, but also suggest that limbic, temporal and parietal regions play a role in the pathophysiology of the disorder. The group x age interaction effects may be the result of altered neuroplasticity.